Cystatin C, a novel cardiometabolic risk marker in women with polycystic ovary syndrome - YILDIZHAN, BEGÜM; ANIK İLHAN, GÖKÇE; PEKİN, TANJU (TAYLOR & FRANCIS LTD, 2016)
Objective: To investigate the impact of urinary albumin excretion (UAE) and cystatin C on the metabolic components of polycystic ovary syndrome (PCOS). Methods: Seventy-five women with PCOS were divided into two groups according to metabolic syndrome as MetS + and MetS-. Clinical, metabolic and renal parameters were compared between the groups. Correlation analyses were performed between cystatin C, microalbuminuria and clinical and metabolic parameters in women with PCOS. Results: Waist/hip ratio (WHR), body mass index, LDL cholesterol, triglyceride, total cholesterol, cystatin C, UAE were significantly higher in the MetS + group compared with the MetS - one. HDL cholesterol was significantly higher in the MetS - group than the MetS + one. The UAE positively correlates with LDL cholesterol, triglyceride and total cholesterol levels. Cystatin C positively correlates with UAE, WHR, LDL cholesterol, triglyceride, total cholesterol levels. Conclusions: Evaluating UAE and cystatin C may be important for the detection of target subjects at high risk for future metabolic syndrome and cardiovascular disease.
Keywords: Cystatin C; metabolic syndrome; microalbuminuria; polycystic ovary syndrome; urinary albumin excretion; METABOLIC SYNDROME; COMPLICATIONS